2021
DOI: 10.1097/bsd.0000000000001139
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Classification of 3D Rib Cage Deformity in Subjects With Adolescent Idiopathic Scoliosis

Abstract: Objective: To analyze patterns of 3D rib cage deformity in subjects with adolescent idiopathic scoliosis (AIS) and their relationship with the spinal deformity.Summary of Background Data: Subjects with AIS present with rib cage deformity that can affect respiratory functions. The 3D rib cage deformities in AIS and their relationship to the spinal deformity are still unelucidated.Methods: A total of 200 AIS and 71 controls underwent low-dose biplanar x-rays and had their spine and rib cage reconstructed in 3-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…In order to distinguish more accurately variations between age intervals, and to separate growing from aging phenomena, the cohort has been divided in two subgroups for gender analysis (growing (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) versus mature skeleton (20 +)) and into five groups for age analysis: Children (8-12 years), Adolescents (13)(14)(15)(16)(17)(18)(19), Young (20-39), Middle-aged (40-59) and Seniors (60 +).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In order to distinguish more accurately variations between age intervals, and to separate growing from aging phenomena, the cohort has been divided in two subgroups for gender analysis (growing (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) versus mature skeleton (20 +)) and into five groups for age analysis: Children (8-12 years), Adolescents (13)(14)(15)(16)(17)(18)(19), Young (20-39), Middle-aged (40-59) and Seniors (60 +).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, thoracic cage should be taken into account when addressing spinal malalignment. It has been demonstrated that restoring kyphosis in spinal deformity corrections helps avoiding respiratory repercussion [13], but the impact of this surgery on the rib cage is not well studied. Indeed, little literature is available about thoracic cage anatomical variations, or its relationship with spinopelvic alignment.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations